Correction of congenital penoscrotal webbing in children: A retrospective review of three surgical techniques. Issue 3 (June 2016) - Bonitz, R.P.; Hanna, M.K.
Summary: Introduction: Congenital penoscrotal webbing (PSW) is a condition that leads to penile shortening and is a common cause of delayed circumcision. While various techniques for PSW repair have been described, no comparative studies are currently available. Objective: The goal of this study was to validate and critique three commonly utilized techniques for PSW repair. Subjects and methods: A retrospective chart review was performed on all patients who underwent repair for PSW, with or without concomitant surgical procedure, by a single surgeon (MKH) over a 7-year period. Inclusion criteria were: aged <5 years, diagnosis of PSW, documented surgical approach undertaken to correct the PSW, and follow-up for a minimum of 6 months. A total of 196 patients aged 6 months–3.4 years (average 7.8 months) were included, and underwent three different types of procedure: Heineke-Mikulicz (HM) scrotoplasty, VY scrotoplasty or Z scrotoplasty. Results: Out of 196 patients, 10 (6.7%) had complications, with four (2.7%) requiring surgical revision or correction. Two patients had excision of 'dog-ear' skin tags, one required excision of a suture tract, and the fourth required revision of skin contraction after HM repair with Z scrotoplasty. Discussion: Congenital penoscrotal webbing is a common condition that often requires pediatric urology consultation. Although it is felt that the severity of the defect may not impact on the operative technique for repair of PSW, data comparing these techniques is lacking. This single-surgeon series highlighted that amongst the patients who underwent one of the three described techniques (HM, VY or Z scrotoplasty), there were no significant postoperative differences in complications or parent satisfaction. Although the ease of the HM repair for minor webbing is acknowledged, Z scrotoplasty is the authors' preference for repair given its ability to address the most severe webbing. Conclusions: In this comparison of three surgical techniques for the correction of PSW, it was demonstrated that each choice is safe, with no option showing a significant difference in complication rate. Surgeon preference should therefore weigh heavily when choosing the surgical approach for PSW repair. Figure Before and after planned surgical technique. Depicted in sequential order is: a Heineke-Mikulicz, V–Y and Z-plasty technique for repair of penoscrotal webbing.